MANAJEMEN RENCANA KEGIATAN PERSIAPAN PEMBANGUNAN PLTN DI INDONESIA - Utomo Utomo (BATAN, 2011)
A feasibi lity Study that has been updated show that two nuclear power uni ts wi th eachuni t of power up to lOOOMWe can represent decently an economical alternative energy supply.It added that the available time schedul e was quite tight so that the preparation for thedevelopment must be starti ng first. Thi s paper will discuss the preparati on of plans of the firstnuclear power plant whi ch includes program activiti es, the structure of contracts, schedules of activities and funding. From the information obtai ned to date that in addition to a candidate site that is ready to be buil t in Muria peni nsula i s sti ll required another potential al ternative site besides to search other compl ete data information. This sit e i nvestigation activi ties completed wi thin the time schedule was passed